Toxic Workplace, Mental Health and Employee Well-being, the Moderator Role of Paternalistic Leadership, an Empirical Study - Mustafa M. Alsomaidaee; Ban Ahmed Joumaa; Khalid Waleed Khalid (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Based on previous research results that recognized the role of paternalistic leadership in promoting a positive work climate, this study explored the impact of a toxic work environment on the mental health and well-being of employees. We used the quantitative methodology to collect and analyze data. A sample of 108 participants from Iraqi internet service provider (ISPs) companies represented the purposive study sample. We targeted employees who experienced the COVID-19 pandemic. All data was collected through an electronic questionnaire (Google and Microsoft Forms). The research model was tested using structural equation modeling (SEM). The results showed a negative effect of the toxic workplace on the mental health of employees. This also had a negative impact on their well-being. The results also indicated that paternalistic leadership has a positive effect on reducing the impact of toxic workplace on employees' mental health. This role was more apparent in modifying the negative relationship between mental health problems and employee well-being. The results showed that workplace bullying, in particular, is less affected by paternalistic leadership practices.